>Education as a Long‐Term Investment: The Decisive Role of Age in the Education‐Growth Relationship. (11th January 2018) - Marconi, Gabriele
Summary: Using a dataset for a panel of 118 countries, this paper shows that changes in the level of education of national populations aged 45 to 64 are positively associated with economic growth. An increase of one percentage point in the share of individuals in this age group who attended secondary education is associated with a 1.2% increase in GDP per capita. In contrast, variation in the level of education in younger cohorts is not positively associated with economic growth. These results suggest that investment in education benefits society, but only in the long‐term. Several possible explanations for this finding are discussed.